PENGEMBANGAN MEDIA PEMBELAJARAN IPA MENGGUNAKAN COCO DIORAMA BERBASIS LIMBAH SABUT KELAPA PADA MATERI SIKLUS AIR DI KELAS V SDN 060800 MEDAN AREA - Refi Yulina; Zainuddin Muchtar; Winara; Laurensia Masri; Lidia Simanihuruk (STKIP Subang, 2026)
This study aims to develop a science learning media in the form of coco diorama that utilizes coconut fiber waste in the water cycle material for fifth grade elementary school students, and to determine the level of validity, practicality, and effectiveness of the media. This study applies the 4D development model (Define, Design, Development, Disseminate). The subjects in this study were 21 fifth grade students of SDN 060800 Medan Area. Data collection techniques were carried out through interviews, observations, questionnaires, and tests. The data analysis used qualitative and quantitative approaches. The results of the study showed that: (1) the coco diorama learning media was considered valid based on the validation results of material experts by 94% and media experts by 89% with the category